Tutorial and Lecture Activities on Deep Online Learning in Dentistry - Febria, Nyka Dwi; Putri, Lulu Hasnadianti (Insisiva Dental Journal: Majalah Kedokteran Gigi Insisiva, 2024)
Online learning has become a new normal in the era of the COVID-19 pandemic. However, this learning mode has brought many challenges that can impact the learning experience. The study aims to evaluate student feedback on the online learning model and identify any challenges that require attention to enhance the quality of Dentistry education at Muhammadiyah University of Yogyakarta. This research is a descriptive observational study that utilized a cross-sectional approach. A modified questionnaire comprising 27 questions was distributed to collect the data. It was found that most of the 277 surveyed students agreed that implementing online learning in tutorial activities had a positive impact. Notably, 47.3% of the students found the online tutorial activities to be an excellent way to learn the material, while an equal number of students, 47.3% believed that they developed their tolerance during the online tutorial group sessions. Furthermore, the student responses to the online lecture activities were also positive, with 40.8% of the students finding comfort in the recorded classes, while 37.2% better understood the material through the online lectures. As for student satisfaction, the majority of the surveyed students expressed their satisfaction with the online learning experience regarding the material 52%, learning strategy 40,4%, availability of e-resources 49,1%, and assistance provided 42,6%.  Students responded positively to online learning in tutorials and lectures and reported overall satisfaction with online learning during the COVID-19 pandemic.